PERORAL FORMS OF CYTOSTATIC DRUGS IN THERAPY OF METASTATIC MAMMARY GLAND CANCER: ROLE IN CLINICAL PRACTICE - G. M. TELETAEVA (Медицинский совет, 2016)
Modern therapeutic approaches allow achieving stable therapeutic effect, extension and maximum long-term preservation of the quality of life of metastatic mammary gland cancer patients. Currently there is no optimal consequence of cytostatic agents use. The advantage of using cytostatic peroral forms is related to easiness of their use in clinical practice, no necessity in venopuncture and reduction of need in hospitalization, as well as with the possibility of a more convenient therapy domiciliary. Due to active use of peroral forms of vinorelbine, fluoropyrimidines, methotrexate, cyclophosphamide, ethopozide, patients received a possibility to choose: to remain in the inpatient hospital or to undergo outpatient therapy domiciliary with minimum changes of the style of life.